Hormone replacement therapy in the group of Polish women aged 45-54 years. Knowledge, opinions, use - Bińkowska, Małgorzata; Pietrzak, Bronisława; Dębski, Romuald (Menopause Review/Przegląd Menopauzalny, 2005)
The aim of the study was to evaluate the level of awareness and attitudes towards hormone replacement therapy (HRT) among women aged 45-54 years. The randomized sample included 1083 women being representative for Polish population. The majority of women (69%) opted for medical intervention in perimenopausal period. Such opinion was presented predominantly by women with university degree of education (88%) and those living in big cities (81%). One third of women accepted hormonal therapy. On the other side, one fourth were against any interventions during this period of life. Only half the women (52%) have known the term menopausal deficiency symptoms, more commonly by those living in big cities. 65% of women declared various level of awareness of HRT. The other 35% reported a total lack of knowledge of this subject. Irrespective of degree of education and place of residence, the main source of information (52%) was gynaecologist, followed by friends or publications in newspapers and magazines (each of 43%). However, the rate of answer I don’t know to detailed questions concerning an effect of HRT on particular organs ranged from 34 to 52. A therapeutic effect on emotional state and physical performance of women was assessed as significantly positive. The majority of women (96%), who had been familiar with HRT opted for this therapy, but 15% of them limited its use only for exceptional situations. Slightly more than half of the women (54%) were of the opinion that this therapy is safe provided that regular follow-up examinations would be carried out. Simultaneously, most women have no their own experience concerning HRT. Only 7% of women use HRT at present and 10% had been on this therapy in the past. 20% of all women stated that they would use HRT in future, including one third of them in the younger age group (45-49 years). Generally, the women were of the opinion that HRT improves quality of life (58%), alleviates depressive states and relieves deficiency symptoms. Main doubts and concerns were associated with potential effects of HRT on the development of certain malignant neoplasms, especially breast cancer and on weight gain. The fundamental reason for beginning of therapy were menopausal deficiency symptoms and advice of gynaecologist. Oral tablets were used most commonly (69%), whereas transdermal patches were applied more rarely (24%). 20% of women were on continuous therapy without bleeding. It had been surprising, that so large number of women declared a complete lack of knowledge of HRT, furthermore, based on answers on some questions, it may be stated that the level of awareness is also inadequate in those women, who declared knowledge of HRT. However, a relatively large group of women, especially aged 45-49 years, is interested in use of HRT in the future.